Comparison of the Effectiveness of Compassion-Focused Therapy and Reality Therapy on the Cognitive Flexibility of Mothers of Children with Autism Spectrum Disorder - Goudarzi, Maryam; Albehbahani, Marjan (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The objective of this study was to compare the effectiveness of compassion-focused therapy and reality therapy in improving cognitive flexibility among mothers of children with autism spectrum disorder.Methods and Materials: This study employed a quasi-experimental design with a pretest–posttest control group. The statistical population consisted of mothers of children diagnosed with autism spectrum disorder in Shiraz in 2025, from whom 90 participants were selected using convenience and voluntary sampling based on predefined inclusion criteria. Participants were randomly assigned to two experimental groups and one control group, each comprising 30 mothers. Cognitive flexibility was assessed at baseline and post-intervention using a standardized self-report questionnaire. The first experimental group received compassion-focused therapy, and the second experimental group received reality therapy; both interventions were delivered in eight structured group sessions over an eight-week period. The control group received no psychological intervention during the study. Data were analyzed using multivariate analysis of covariance to control for pretest scores and examine between-group differences at posttest.Findings: Inferential analyses revealed a statistically significant effect of group membership on posttest cognitive flexibility after controlling for baseline scores. Both compassion-focused therapy and reality therapy resulted in significantly higher cognitive flexibility scores compared with the control group. Moreover, a significant difference was observed between the two experimental groups, indicating that compassion-focused therapy produced greater improvements in cognitive flexibility than reality therapy. The effect size for the overall intervention effect was in the moderate range, suggesting clinically meaningful differences attributable to the therapeutic approaches.Conclusion: The findings indicate that both compassion-focused therapy and reality therapy are effective interventions for enhancing cognitive flexibility in mothers of children with autism spectrum disorder, with compassion-focused therapy demonstrating superior efficacy.